New study dehydration of soft histological specimens - Al-Hussany, Baha F. (The Iraqi Journal of Veterinary Medicine, 2005)
This study represent a new process for dehydration of the histologicalspecimen that knowledge and used in the laboratory study . Technical andmedical research will be set up a completely great scientific and to addition ofthis to make an experiment , to a shortness the time and the material cost that isused in the different stage of dehydration and these for the soft tissue ( only ) .